Mechanical testing and engineering applicability analysis of SAP concrete used in buffer layer design for tunnels in active fault zones - Jun Cao; Zheshu Wu; Zhen Cui; Xiancheng Mei (Reviews on Advanced Materials Science, 2024)
To tackle the challenge of dislocation damage when tunnels traverse active fault zones, this study introduces the concept of using brittle buffer materials for anti-dislocation. Building on this concept, we propose a novel concrete buffer material utilizing large-sized spherical super absorbent polymers (SAP) as a porogen, aimed at ensuring the safety of tunnel structures during active fault dislocations. To investigate the feasibility and superiority of SAP concrete as a buffer material compared to other similar materials, we prepared samples with three different SAP concrete proportions and conducted a series of physical and mechanical tests. The results show that SAP pre-hydrated with 0.2 mol·L−1 sodium carbonate solution exhibits a slower rate of moisture loss in the cement slurry, aiding the hydration reaction of concrete. The permeability coefficient of SAP concrete is approximately 10−7 cm·s−1, slightly lower than foam concrete of the same density level. SAP concrete buffer material demonstrates significant brittleness, in contrast to the mostly ductile nature of other buffers such as foam concrete and rubberized concrete. Utilizing the brittle nature of SAP concrete materials, when applied to tunnels affected by stick–slip active fault dislocations, its instantaneous loss of compressive capacity provides excellent yield performance, thus protecting the tunnel lining from damage. However, under certain circumferential pressure conditions, both the peak and residual strength of SAP concrete significantly increase. High peak and residual strengths do not favor the effective buffering effect of SAP concrete; therefore, an approach involving the intermittent arrangement of precast buffer blocks has been proposed for application.